natural dos campos rupestres da Serra Norte de Carajás, Pará, Brasil The effect of seasonality of rainfall in the floristic and structure of natural regeneration of the rupestrian fields of the Sierra Norte de Carajás, Pará, Brazil - Chaves, Priscilla Prestes; Ferreira, Leandro Valle (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Few studies have been conducted on Amazon compared to the variation in the structure and floristic communities of natural regeneration relative seasonality of precipitation and no study has been conducted in the rocky fields of the Amazon. The aim of this study is to compare the floristic and structure of natural regeneration community vegetations of rocky fields and seasonal ponds, between periods of drought and rainy in the Sierra Norte de Carajás, Brazil. Sampling occurred in two seasons (rainy and dry). In stony fields were identified 67 species, 46 and 33 species, between dry and rainy seasons, respectively. In Seasonal ponds were identified 61 species, ranging from 30 to 41 species, among the dry and rainy season, respectively. There was no significant difference in the number of individuals and the richness and diversity of species in the rocky fields and seasonal ponds between periods of drought and rainy. However, there is a great change in species composition, in both types of vegetation, between periods of drought and rainy. This demonstrates that communities of natural regeneration in both types of vegetation are clearly adapted to abiotic variations caused by the wide variation in the amount of rainfall.